Persepsi Guru Al Amien Prenduan tentang Akad Mudharabah di BNI Syari’ah Sumenep - Ning Kholisotul Ilmi; Ridho Sugiyono (Rechtenstudent, 2020)
The development of sharia banking has become a measure of the success of the sharia economy. Syharia banks have a function as channeling funds to the community and collecting funds from the community. In sharia banking, there are several contracts that have been implemented, one of which is mudharabah contract. Mudharabah contract is a business cooperation between two parties where the first party (shahibul maal) provides the capital while the second party becomes the manager (mudharib). The purpose of this study is to find out more about the teacher Al Amien Prenduan's perceptions of the mudharabah contract that has been implemented at BNI Sharia Sumenep. The researchers use a case study qualitative research. The methods used are interview and documentation methods. The results show, the majority of teachers at Al Amien Prenduan used savings at the BNI Sharia Sumenep bank. Knowledge of the existence of sharia banks is evident in the form of savings which are mostly used by Al Amien Prenduan teachers. However, the promotion carried out by the sharia bank is felt by the teacher Al Amien Prenduan. The Al Amien Prenduan teachers’ understanding of mudharabah contract is felt to be less influencing perceptions of the operational system and also the way of services provided. Meanwhile, Al Amien's teacher do not understand more deeply about mudharabah contract, among others, due to lack of information and lack of socialization from the financial institution.